Challenges and Ways to Improve Availability of Transport for Small Partnerships - V. Enin, D. (International Journal of Engineering and Technology, 2018)
The present paper discusses results of the studies on establishment of the main reasons for access limitations of transport, including pedestrian communications, and for people with limited mobility in Russia. It suggests the main ways to solve the problems identified. In this paper, transport means a system that includes: vehicles, transport infrastructure facilities, transport and pedestrian communications, information support, services and personnel in transport.Â Â